DYNAMICS OF PROFESSIONAL SELF-CONSCIOUSNESS OF PEDAGOGICAL COLLEGE STUDENTS (Psychology Travelogs, 2024)
The professional self-consciousness of pedagogical college students is represented by a set of three components: cognitive, affective and behavioural. The cognitive component is represented by characteristics that reflect the expression of professionally important traits, the actualisation of the image of the ideal self, as well as parameters that allow assessing the level of professional identity. The affective-evaluative component characterises the subject's self-attitude as a student of a pedagogical college, as well as the attitude to his/her educational activity. The behavioural component reflects motivational and value, regulatory and action aspects that determine the success of professional activity. In the process of professional training in a pedagogical college, one can observe the dynamics of students' professional identity formation.In the process of professional training at a pedagogical college, one can observe the dynamics of students' professional identity formation. First of all, it is manifested in the change of the content of each of its components. The cognitive component demonstrates a gradual transition from formal and attributive (i.e. superficial) ideas to the formation of holistic ideas about future professional activity. Professional identity begins to form a year after entering college and reaches its acme in the final year. The image of a professional formed in the first year of study remains unchanged throughout the entire period of study. The peculiarities of the content of the structural components of professional self-consciousness, as well as the peculiarities of the factor structure, allowed to determine the main directions of work on psychological and pedagogical support of professional self-consciousness of students of the pedagogical college at each course of study.
Keywords: professional self-consciousness; pedagogical college students; cognitive component; affective-evaluative component; behavioural component